2013
DOI: 10.7883/yoken.66.299
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Genetic Diversity of Influenza A(H1N1)pdm09 Virus Circulating during the Post-Pandemic Period in Turkey

Abstract: SUMMARY:The aimes of the present study were to monitor genetic alterations in the hemagglutin (HA) gene and oseltamivir resistance-related alterations in the neuraminidase (NA) gene of influenza A(H1N1)pdm09 viral isolates detected during the post-pandemic period in Turkey. A total of 2601 clinical specimens obtained from suspected cases of influenza A(H1N1)pdm09 viral infections were analyzed by real-time reverse transcription polymerase chain reaction. Viral RNA was detected in 233 (9z) clinical specimens. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…A less common S185P mutation was seen instead of S185T in 10% of our isolates, and we also identified rare mutations (C4S, T72A, I96V, N260D, I266F, L314M, S326F in HA1 and I45V, V66A, R106K, F140L in HA2) in individual isolates. Notably, neither the D222G mutation previously associated with increased virulence, nor the mutations (A186T, R205K, D222E/N, V249L) observed in Turkish isolates of 2009 and 2010‐2011 influenza seasons were detected in our isolates.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…A less common S185P mutation was seen instead of S185T in 10% of our isolates, and we also identified rare mutations (C4S, T72A, I96V, N260D, I266F, L314M, S326F in HA1 and I45V, V66A, R106K, F140L in HA2) in individual isolates. Notably, neither the D222G mutation previously associated with increased virulence, nor the mutations (A186T, R205K, D222E/N, V249L) observed in Turkish isolates of 2009 and 2010‐2011 influenza seasons were detected in our isolates.…”
Section: Discussioncontrasting
confidence: 66%
“…In the 2009‐2010 and 2010‐2011 seasons, the HA nucleotide sequence similarity rates between Turkish isolates and the A/California/07/2009 virus were >98.9% and >98.7%, respectively, but the similarity ranging 96.6% to 97.2% we observed in the 2015‐2016 season was pointing out a rising divergence from the progenitor virus compared to the previous seasons. Accordingly, the total number of amino acid mutations (14 common, 1 less common, and 11 rare) in the 2015‐2016 season was higher than of the previously reported by Guldemir et al The 90%‐100% of our isolates carried 14 common mutations (P83S, S84N, D97N, S162N, K163Q, S185T, S203T, I216T, A256T, K283E, I321V in HA1 and E47K, S124N, E172K in HA2). These mutations have been previously reported from different parts of the world in isolates of the same period .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Phylogenetic analysis of the 2009 pandemic H1N1 virus (H1N1pdm09) indicated that the genome was a combination of gene segments that had not been previously identified in animal or human influenza viruses (5). The HA gene of H1N1pdm09 belongs to the classical swine lineage distinct from other viruses of human or avian origin that were introduced into pigs more recently, giving rise to 'human-like' and 'avianlike' swine influenza lineages (18).…”
Section: Introductionmentioning
confidence: 99%